Three 3D Co(ii) cluster-based MOFs constructed from polycarboxylate acids and bis(imidazole) ligands and their derivatives: magnetic properties and catalytic performance for the ORR. Issue 35 (21st August 2019) - Yang, Ming-Xing; Chen, Li-Juan; Ma, Rong; Cai, Jian-Nan; Shi, Yuan-De; Lin, Shen
Abstract : Three 3D Co-MOFs constructed from polycarboxylate acids and bis(imidazole) ligands were prepared by urothermal synthesis and the derived porous carbon material shows comparable electrocatalytic property toward the ORR. Abstract : Three 3D polymeric complexes containing polynuclear Co(ii ) units, [Co3 (bpda)3 (bib)2 ]·H2 O (1 ), [Co5 (OH)2 (H2 O)2 (bpda)4 (bib)2 ]·2H2 O (2 ), and [Co2 (OH)(bib)(bpt)]·H2 O (3 ) (H2 bpda = biphenyl-2, 4′-dicarboxylic acid, H3 bpt = biphenyl-3, 4′, 5-tricarboxylic acid, bib = 1, 4-bis(1-imidazolyl)benzene), have been prepared by urothermal synthesis. Complex1 exhibits an unusual (4, 6)-connected 3D network based on binuclear Co(ii ) clusters and Co 2+ centers bridged by bpda 2− and bib ligands. Complex2, containing a novel pentanuclear Co(ii ) cluster, features a porous 3D MOF with a regular nanosized tunnel. Complex3 contains an interesting tetranuclear Co(ii ) cluster and displays an amazing 3D porous MOF built from double-layered 2D [Co2 (μ3 -OH)(bpt)3 ] n networks pillared by two rows of bib spacers. In the title complexes, polycarboxylate acids serve to construct and stabilize the polynuclear Co(ii ) clusters, while bis(imidazole)s help to expand the dimensionality of MOFs. Complexes2 and3 show antiferromagnetic properties. Compound3 with high surface area, high yield, high purity, and high chemical stability was used as a precursor to fabricate Co, N-codoped porous carbon materials by simple carbonization under an Ar atmosphere. The catalytic properties of the Co, N-codoped porous carbon material derived from complex3 (denoted as CoNC-3) as an ORR electrocatalyst were studied. CoNC-3 displays superior electrocatalytic performances for the ORR.